WORKLOAD ANALYSIS TO OPTIMIZE LABOR OF TOFU FACTORY X WITH WORK LOAD ANALYSIS AND WORKFORCE ANALYSIS METHODS - Cindy Meisya; Nur Fajriah Fajriah; Santika Sari (Journal of Industrial Engineering Management, 2022)
Tofu factory X is one of the industries in the food sector. This factory processing soybeans into tofu. Tofu factory X is one of the tofu factories located in Depok, West Java. The problems that occur in this factory are the working hours that exceed the normal limit and do not achieve the optimal productivity levels due to the factory's inability to fulfill all demands, for this reason this research aims to calculate the workload of each worker in order to know the optimal number of workers according to the workload with Work Load Analysis and Workforce Analysis method, after that, a cost analysis is carried out to assist decision making. Based on the results of the analysis, it is found that there are 4 workers who have a workload that exceeds the normal limit, there are operator 1 with 124%, operator 4 with 116%, operator 5 with 112%, and operator 7 with 111%. The calculation of the optimal workforce using the Workforce Analysis method shows that the workers of the tofu factory X are advised to add 4 people to each work station with excessive workloads. Based on the cost analysis, the alternative with the lowest cost was chosen by adding overtime hours with details of the costs that came out per two months amounting to RP.5.271.676.3